A Case of Concurrent Riedel's, Hashimoto's and Acute Suppurative Thyroiditis. (11th August 2009) - Pirola, I.; Morassi, M. L.; Braga, M.; De Martino, E.; Gandossi, E.; Cappelli, C.
Abstract : Riedel's thyroiditis (RT) is a rare form of infiltrative and inflammatory disease of the thyroid, first described by Bernard Riedel in 1896. The concurrent presence of RT and other thyroid diseases has been reported, but, the association of RT with Hashimoto's thyroiditis and acute thyroiditis has not yet been reported. We present a case of concurrent Riedel's, Hashimoto's and acute thyroiditis that occurred in a 45-year-old patient.